(untitled) (Revista de Ciências Agroveterinárias, 2020)
Among the native fruit trees of the South of Brazil, the red strawberry guava (Psidium cattleyanum Sabine) of the Myrtaceae family and it is considered a native forest species of great importance in this region. The strawberry guava is usually propagated through sexual reproduction, however, few studies have been done to optimize the propagation of this native species. In addition to this problem, many studies with woody plants have shown positive results with propagation through tissue culture techniques. In this way, the objective was to verify the in vitro germination of red strawberry guava and the initial development of the explants with the use of the micropropagation technique. A completely randomized design with 3 x 2 factorial arrangement was used, with three forms of seed fractionation (without cutting, longitudinal and transverse cutting) and two conditions of light intensities (presence and absence of light), totaling six treatments with 10 replications of four seeds each. After 14 days of the experiment were evaluated oxidation (%) and sowing (cm). The seeds germination rate (%), mean root length (cm), length of the largest root (cm), length of explant and number of roots and leaves were analyzed with 240 days. It was concluded that just a single seed of Psidium cattleyanum, when being fractionated, maintains the germinative capacity and can produce more than one normal seedling, in order to have a larger number of seedlings, from a smaller number of seeds. In addition, it was verified that regardless of the fractionation or not of the red spider seeds, direct light conditions provided roots of greater length, as well as a larger number of leaves in the explants.